2015
DOI: 10.1038/pj.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between fragility and cooperativity in segmental dynamics of glass-forming para-substituted polystyrenes

Abstract: To understand the mechanism of the viscous slowdown in supercooled liquids that is responsible for glass transition, we investigate the interrelation between glass transition temperature T g , fragility, and cooperativity in segmental dynamics. Polymeric glass-formers having a similar chemical structure are expected to exhibit clear correlations between the above parameters. In this paper, polystyrene (PS) derivatives possessing various para-substituents are studied using calorimetry in regard to the fragility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…Hence, it is reasonable to conclude that IL microscopic parameters (quantified by λ and D/D blk ) plays a considerable role in tuning the m and DH of the PNC system. Importantly, our report provides an evidence of anti-correlation between fragility and dynamical heterogeneity which is contrary to most recent reports in other types or glasses or PNCs [5,25]. These results also points to the predominance of kinetic fragility in our entropic PNC systems which was alluded to occur in some amorphous polymers earlier [26] but has not been observed in most other PNC systems.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Hence, it is reasonable to conclude that IL microscopic parameters (quantified by λ and D/D blk ) plays a considerable role in tuning the m and DH of the PNC system. Importantly, our report provides an evidence of anti-correlation between fragility and dynamical heterogeneity which is contrary to most recent reports in other types or glasses or PNCs [5,25]. These results also points to the predominance of kinetic fragility in our entropic PNC systems which was alluded to occur in some amorphous polymers earlier [26] but has not been observed in most other PNC systems.…”
Section: Resultscontrasting
confidence: 99%
“…Another key dynamical parameter, which has been widely used to describe glasses and supercooled liquids, including polymers and PNCs, is dynamic heterogeneity (DH) [22][23][24]. In the case of enthalpic PNCs, m seems to correlate with DH (increases for attractive and decreases for repulsive interactions) quantified in terms of a temperature dependent dynamical length scale, ξ, which seems to grow moderately on approaching the glass transition [5,19,24,25]. On the other hand some studies suggest that DH decreases with increasing fragility [26] in amorphous polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of the data is noticeable for α 1 and α 2 compared with α 3 and α 4 , which suggests that the assumptions of α 3 and α 4 are more appropriate than those of α 1 and α 2 . The above behavior of m may be related to the relationship between the fragility and the dynamic length scale at T g [ 29 , 55 , 56 , 57 ]. The coupling energy ε , which denotes the ability of dynamical coupling between segments, can be regarded as the cohesive energy [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many works investigate the relationships between the glass transition temperature, the fragility index, and the cooperativity in polymers. Sasaki et al, for instance, show that in PS derivatives the size of the cooperative rearranging regions (CRR) increases with increasing fragility. Recent investigations showed that m is a key parameter to evaluate the molecular arrangement and the relaxation dynamics of amorphous phases, for it is supposed to be strongly dependent on the packing efficiency of the macromolecules as well as on the stiffness of their backbone .…”
Section: Results and Discussionmentioning
confidence: 99%